2008
DOI: 10.1002/glia.20688
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tmem10/Opalin as an oligodendrocyte enriched gene using expression profiling combined with genetic cell ablation

Abstract: SUMMARY Oligodendrocytes form an insulating multilamellar structure of compact myelin around axons, which allows efficient and rapid propagation of action potentials. However, little is known about the molecular mechanisms operating at the onset of myelination and during maintenance of the myelin sheath in the adult. Here we use a genetic cell ablation approach combined with Affymetrix GeneChip microarrays to identify a number of oligodendrocyte-enriched genes that may play a key role in myelination. One of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 48 publications
(77 reference statements)
4
53
0
Order By: Relevance
“…Previous studies showed Fa2h expression in oligodendrocytes by in situ hybridization (Eckhardt et al 2005) and by immunoblot (Alderson et al 2006). More recent gene expression profiling studies also showed Fa2h expression in oligodendrocytes (Golan et al 2008; Howng et al 2010; Stritt et al 2009). Nonetheless, our finding that the learning and memory deficits are present only in Fa2h −/− mice and not in Fa2h flox/flox Cnp1-Cre mice could not be explained by the loss of FA2H function in oligodendrocytes.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies showed Fa2h expression in oligodendrocytes by in situ hybridization (Eckhardt et al 2005) and by immunoblot (Alderson et al 2006). More recent gene expression profiling studies also showed Fa2h expression in oligodendrocytes (Golan et al 2008; Howng et al 2010; Stritt et al 2009). Nonetheless, our finding that the learning and memory deficits are present only in Fa2h −/− mice and not in Fa2h flox/flox Cnp1-Cre mice could not be explained by the loss of FA2H function in oligodendrocytes.…”
Section: Discussionmentioning
confidence: 87%
“…Dissociated spinal cord cells were prepared from mice embryos at day 13.5 of gestation as described recently (Golan et al, 2008;Thomson et al, 2008). OL precursor cells (OPCs) were isolated and maintained essentially as described by McCarthy and de Vellis (1980).…”
Section: Materials and Methods Cell Culturementioning
confidence: 99%
“…Before staining, cells were postfixed with methanol at 2208C for 10 min or with Bouin's fixative (Sigma) for 1 min. Immunofluorescence was carried out as previously described (Eshed et al, 2005;Brockschnieder et al, 2006;Golan et al, 2008). The following monoclonal antibodies were used: MAG (1:300; Boehringer, Mannheim, Germany), RIP (1:1,000; The Developmental Studies Hybridoma Bank), gliomedin (1:250; Eshed et al, 2005), bIII tubulin (TUJ 1; 1:1,000; Convance, Berkeley, CA), Caspr (1:300; Poliak et al, 1999), and rat anti-MBP (1:250; Chemicon).…”
Section: Immunofluorescencementioning
confidence: 99%
“…It has been shown that one of the identified proteins, transmembrane protein 10 (Tmem10; also known as Opalin or oligo dendrocyte paranodal loop protein), whose expres sion is specific to the brain, predominantly localized in many white matter regions and was upregulated during the postnatal developmental stages [2]. It was shown that Opalin protein is specifically expressed by myelinating oligodendrocytes, suggesting that it plays a unique role in mammalian myelin [11]. In the CNS the main proteins of myelin are proteolipid protein (PLP), myelin basic protein (MBP) and myelin oligo dendrocyte glycoprotein (MOG).…”
Section: Introductionmentioning
confidence: 99%
“…As Opalin is a unique molecular marker for mature oligodendrocytes and MOG is a component of the myelin sheath which is an important autoan tigen linked to the pathogenesis of MS [11,20], we aimed to examine the in vivo effects of LIF on the remyelination process in the cerebral cortex of the cuprizoneinduced MS mouse.…”
Section: Introductionmentioning
confidence: 99%